Experiencing Nature through Immersive Virtual Environments: Environmental Perceptions, Physical Engagement, and Affective Responses during a Simulated Nature Walk - Calogiuri, Giovanna; Litleskare, Sigbjørn; Fagerheim, Kaia A.; Rydgren, Tore L.; Brambilla, Elena; Thurston, Miranda (Frontiers in Psychology, 2018)
By combining physical activity and exposure to nature, green exercise can provide additional health benefits compared to physical activity alone. Immersive Virtual Environments (IVE) have emerged as a potentially valuable supplement to environmental and behavioral studies, and might also provide new approaches to green exercise promotion. However, it is unknown to what extent green exercise in IVE can provide psychophysiological responses similar to those experienced in real natural environments. In this study, 26 healthy adults underwent three experimental conditions: nature walk, sitting-IVE, and treadmill-IVE. The nature walk took place on a paved trail along a large river. In the IVE conditions, the participants wore a head-mounted display with headphones reproducing a first-person 360˚ video and audio of the nature walk, either sitting on a chair or walking on a manually driven treadmill. Measurements included environmental perceptions (presence and perceived environmental restorativeness –PER–), physical engagement (walking speed, heart rate, and perceived exertion), and affective responses (enjoyment and affect). Additionally, qualitative information on the experience of using IVE was collected through open-ended questions. The participants rated the IVEs with satisfactory levels of ‘being there’, ‘realism’ and ‘sense of reality’, but also reported discomforts such as ‘flatness’, ‘motion lag’ and ‘cyber sickness’. With equivalent heart rate and walking speed, participants reported higher perceived exertion in the IVEs than in the nature walk. Moreover, despite equivalent ratings of PER in the nature walk and in the IVEs, the latter were perceived as less enjoyable and led to worsened affect profile. Presence and PER did not differ between the IVEs, although in the treadmill-IVE participants had smaller reductions in positive affect. In both the IVEs, the negative affective responses were mainly associated with cyber sickness, whereas the PER components were positively associated with enjoyment. From the qualitative analysis, it emerged that poor postural control and lack of a holistic sensory experience can also hinder immersive experience in the IVEs. The results indicate that IVE technology might in future be a useful instrument in green exercise research and promotion, but only if improvements in the image quality and avoidance of cyber sickness can be addressed.